1978
DOI: 10.1136/gut.19.12.1105
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 binding protein as a tumour marker for hepatocellular carcinoma.

Abstract: SUMMARY Grossly raised levels of tumour related vitamin B12 binding protein, reflected by rises in serum vitamin B12 and unsaturated vitamin B12 binding capacity (UBBC), were found in three of 44 patients with hepatocellular carcinoma. All three were HBsAg negative and had normal serum alpha fetoprotein levels. The patients did not have underlying cirrhosis and the tumours contained characteristic intracellular inclusions. In the first patient the UBBC level fell during a paitial remission induced by adriamyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…Waxman and Gilbert [1] sug gested that the increase in serum UBBC in hepatoma is due to a hepatoma Bi 2-binding protein which is closely related to UTC I. This observation has been supported by Kane et al [3]. Both authors claimed that the difference between the hepatoma Bi 2-bind ing protein and UTC I lies in the absolute increase of sialic acid content in the hepa toma B!…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Waxman and Gilbert [1] sug gested that the increase in serum UBBC in hepatoma is due to a hepatoma Bi 2-binding protein which is closely related to UTC I. This observation has been supported by Kane et al [3]. Both authors claimed that the difference between the hepatoma Bi 2-bind ing protein and UTC I lies in the absolute increase of sialic acid content in the hepa toma B!…”
Section: Discussionsupporting
confidence: 67%
“…myeloproliferative disorder, acute leukemia [15], and sickle cell disease [16], where strong correlations have been reported. This lack of correlation be tween UTC I and WBC in our hepatoma patients lends weight to the observations of Waxman et al [2] and Kane et al [3] that the increase of UBBC and UTCI in hepatoma is not due to leukocytosis, but due to a special hepatoma Bn binder which is derived from granulocytes and sialylated during transit through the malignant hepatocytes. Our ob servation agrees with Nexo et al [13], Kane et al [3] and Norredam et al [14] that the abnormality of B)2-binding protein in hepa toma is not confined to children and adoles cents alone.…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…Studies suggest that B12 vitamin has a hepatoprotective effect on liver cirrhosis patients (18) and that the dosage of the serum levels could be used as a prognostic marker for followup of HCC patients with regular alpha-fetoprotein levels (20) . However, there are conflicting studies in the literature, with authors that have observed reduction in B12 vitamin levels in HCC patients (22) .…”
Section: Discussionmentioning
confidence: 99%